2021
DOI: 10.3390/foods10020399
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a Fast Screening Method of the Varietal Origin of Olive Oil: The Usefulness of an NMR-Based Approach

Abstract: This work encompasses the use of 1D multinuclear NMR spectroscopy, namely, 1H NMR and 13C NMR DEPT 45, combined with a multivariate statistical analysis to characterize olive oils produced from nine different varieties: Galega Vulgar, Cobrançosa, Cordovil de Serpa, Blanqueta, Madural, Verdeal Alentejana, Arbequina, Picual and Carrasquenha. Thus, the suitability of an NMR-based spectroscopic tool to discriminate olive oils according to their varietal origin is addressed. The results obtained show that the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…27 Recently, the varietal origin of olive oils using a NMR-based approach was successfully demonstrated for Portuguese varietal olive oils using 1 H and 13 C NMR DEPT 45 spectroscopy, combined with a multivariate statistical analysis. 28 Furthermore, the fusion of data from different analytical techniques is expected to improve the discrimination of origin through a synergetic effect of complementary information, using multiblock predictor and multiblock response. In the literature, several strategies have been proposed and classified into low-level (or variable level), mid-level (or factor level), and high-level (or decision level) data fusion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Recently, the varietal origin of olive oils using a NMR-based approach was successfully demonstrated for Portuguese varietal olive oils using 1 H and 13 C NMR DEPT 45 spectroscopy, combined with a multivariate statistical analysis. 28 Furthermore, the fusion of data from different analytical techniques is expected to improve the discrimination of origin through a synergetic effect of complementary information, using multiblock predictor and multiblock response. In the literature, several strategies have been proposed and classified into low-level (or variable level), mid-level (or factor level), and high-level (or decision level) data fusion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, Merchak et al demonstrated that 13 C insensitive nuclei enhancement by polarization transfer (INEPT) has a higher potential than 1 H NMR in the classification of olive oils according to the altitude of the olive plantations . Recently, the varietal origin of olive oils using a NMR-based approach was successfully demonstrated for Portuguese varietal olive oils using 1 H and 13 C NMR DEPT 45 spectroscopy, combined with a multivariate statistical analysis …”
Section: Introductionmentioning
confidence: 99%
“…CF I G U R E 2 1 H NMR spectrum at 400 MHz of the lipidic fraction of extra virgin olive oil (EVOO) obtained with a simple proton experiment TA B L E 2 Peak assignments of the monodimensional lipid spectrum reported in Figure2(Cabrita et al, 2021) protons (α and α') of the glycerol unit of TAGs (-CH 2…”
mentioning
confidence: 99%
“…Despite the aim of this Special Issue encompassing three key topics-specificity, authenticity, and adulteration-no contributions were received regarding the theme of specificity. Thus, this editorial has collected papers giving an interesting outlook on several promising methodologies, including NMR-based approaches [2,3], chromatographic techniques [4][5][6][7], and stable isotope analysis [8] combined with advanced statistical modelling techniques for addressing the geographic and varietal origin of olive oils and cultivar differentiation, highlighting the themes of authenticity and traceability. Researchers have also devoted their attention to some classes of target compounds that are present in olive oils, namely volatiles [6], n-alkanes and n-alkenes [5], triacylglycerols [2], and biophenols [7].…”
mentioning
confidence: 99%
“…Thus, this editorial has collected papers giving an interesting outlook on several promising methodologies, including NMR-based approaches [2,3], chromatographic techniques [4][5][6][7], and stable isotope analysis [8] combined with advanced statistical modelling techniques for addressing the geographic and varietal origin of olive oils and cultivar differentiation, highlighting the themes of authenticity and traceability. Researchers have also devoted their attention to some classes of target compounds that are present in olive oils, namely volatiles [6], n-alkanes and n-alkenes [5], triacylglycerols [2], and biophenols [7]. Their role in the discrimination between olive oils based on geographic origin and cultivar, using advanced analytical techniques, has been investigated.…”
mentioning
confidence: 99%